Management of Commonwealth leased office property : Department of Finance - Australian National Audit Office (Barton, ACT : Australian National Audit Office, 2018)
The objective of the audit was to assess whether effective arrangements have been established by Finance to achieve value for money outcomes for Commonwealth leased office property.
Series title on cover: Performance audit report.
Includes bibliographical references.
Also available online. Address as at 29/01/2019
Keywords: Department of Finance -- Auditing; Office leases -- Australia; Executive departments -- Australia -- Buildings; Australian